AI Literature: the disenchantment of word and the enchantment of code. - Tao, Feng (Neohelicon, 2024)
Artificial intelligence literature refers to the automatic writing of artificial intelligence that produces literary works. The emergence of AI literature leads to the disenchantment of word and also leads to the enchantment of code. AI literature is closely linked to AI natural language processing technology, the essence of which lies in the automatic generation of words and the combination of words. AI has no actual human author, which allows for a reader-centred reception theory as its key interpretive theory. The acceptance of AI texts as literature is also due to a secondary consensus on the form of literature and the sense of ritual. The charming of code embodies the infinite trust and excessive worship of technology and certainty, and to disarm it, it also necessarily requires the analysis and regulation of code. AI literature is more often noticed as an artistic event, and this artistic event is the disenchantment of art and the enchantment of technology.